Immunoproteasome components LMP2, PSME1, and PSME2 as novel tissue biomarkers predicting response and survival in neoadjuvant chemoimmunotherapy for resectable NSCLC - Xie, Ru; Zhai, Ke; Yu, Jinming; Zhao, Miaoqing (Frontiers in Immunology, 2025)
BackgroundWhile neoadjuvant chemoimmunotherapy (NACI) improves outcomes in resectable non-small cell lung cancer (NSCLC), a significant subset of patients exhibits innate resistance. Biomarkers predicting response are urgently needed. Given the central role of antigen processing in immunotherapy efficacy, we investigated key immunoproteasome components—LMP2 (PSMB9), PSME1, and PSME2—as potential tissue-based biomarkers for NACI response and survival.MethodsPotential biomarker genes were identified through systematic literature review of NSCLC immunotherapy transcriptomic datasets. Candidate genes underwent validation in public databases (GEO, TCGA) via differential expression and Kaplan-Meier survival analysis. Protein expression of LMP2, PSME1, and PSME2 was assessed by immunohistochemistry (IHC) in pre-treatment tumor biopsies from a retrospective cohort of 50 resectable NSCLC patients treated with NACI (platinum-based chemotherapy + anti-PD-1/PD-L1). Pathologic response was categorized as major pathologic response (MPR, ≤10% residual viable tumor) or incomplete pathologic response (IPR). Associations with MPR, overall survival (OS), and independent prognostic value were evaluated.ResultsBioinformatic analysis identified LMP2, PSME1, and PSME2 as immunoproteasome subunits linked to antigen presentation pathways. In the clinical cohort, low pre-treatment intratumoral expression of LMP2, PSME1, and PSME2 (by IHC) significantly predicted MPR (P < 0.05). Specifically, IPR patients exhibited higher median IHC scores for all three proteins compared to MPR patients. Kaplan-Meier analysis demonstrated that high pre-treatment LMP2 expression was associated with significantly improved OS (median OS: Not Reached vs. 40.0 months, P <0.0104). Post-NACI pathological stage (ypTNM III-IV) correlated with worse OS (P = 0.0027). Multivariate Cox analysis confirmed MPR status (HR = 8.709, P = 0.003), and high pre-treatment LMP2 (HR = 0.051, P = 0.007) as independent prognostic factors for OS.ConclusionLow pre-treatment expression of immunoproteasome subunits LMP2, PSME1, and PSME2 predicts favorable pathologic response to NACI in resectable NSCLC. High baseline LMP2 expression, along with MPR achievement, independently associates with improved survival. These findings nominate LMP2/PSME1/PSME2 as novel, IHC-detectable biomarkers for stratifying NACI response and prognosis, highlighting the critical role of antigen processing machinery in modulating treatment efficacy. Validation in larger prospective cohorts is warranted.